A ampliação do acesso à justiça e o judiciário contemporâneo - Otharan, Luiz Felipe Rosa (2012)
The present research aims to analysis of qualitative and quatitative expansion of access to Justice and the Judiciary contemporary, checking some consequences of the phenomenon ocurred. It starts from a study of individualism, patrimonialism, separation of powers and legal certainty, which served as pillars of suport to the Liberal State. It talks about the history of the formation of the liberal state and the task of the Judiciary that time. It examines the increasing importance of the Judiciary and the crisis of the Legislative Branch of recent years, that led to the abandonment of the model proposed by the Liberal State. It explore the quantitative and qualitative expansion of acess to justice, which are, in short, the massification of torts and the interference of the Judiciary Branch in any disputes, respectively. Finally, it investigates the consequences of the events mentioned. It examines the current situation that legal certainty does not exist, due to the abandonment of rules as the only which can provide legal certainty and the expansion of the powers of the Judiciary. It analyses the search for a legal certainty through a proposal for a precedent system inspired in common law.